Etiologic Characteristics of Influenza Epidemics on the Territory of Russia in the Period of Pandemic COVID-19 in 2020–2023 - P. A. Petrova; N. I. Konovalova; A. Y. Boyarintseva; D. M. Danilenko; A. D. Vasilieva; T. N. Shelepanova; A. V. Prokopets; M. Y. Eropkin (Эпидемиология и вакцинопрофилактика, 2024)
Relevance. The improvement of the surveillance of evolution of influenza viruses and the refinement of the capacity of prognostics of their evolutionary tendencies would lead to the better understanding and control on influenza epidemics. Aim. Establish the etiological nature of influenza epidemics in 2020–2023 in Russia and the antigenic properties of influenza viruses of the types A and B which circulated on its territory in 2020–2023. Methods. Isolation of influenza viruses from PCR+-clinical materials (nazo-pharingeal swabs and post-mortem tissue samples) in the cell lines MDCK and MDCK-Siat1; antigenic analysis by means of the reaction of hemagglutination-inhibition (HI) and micro-neutralization (MN) with the cell-ELISA detection using the post-infectious ferret antisera and rat polyclonal antisera; antigenic cartography. Results and discussion. The season 2020–2021 – the 1st season of pandemic of COVID-19, was characterized by quasi-total disappearance of influenza viruses from human population on the territory of REussia, probably as a consequence of stringent sanitary-hygienic measures worldwide due to COVID-19 pandemic. In the next epidemic season we could observe the domination of influenza viruses A(H3N2) during all season with the slight growth of the proportion of influenza B in the second part of the season. We could not isolate influenza viruses A(H1N1)pdm09 in that season due to their low epidemic activity, and the majority of isolated strains were А(H3N2) viruses – 94,4% of the total number of isolates. Influenza Вvic consisted 28 % of all number of isolates. The season 2022-23, opposite to the previous one, was characterized by the domination of influenza viruses of the sub-type А(H1N1)pdm09 what made it different from the epidemic in Europe and North America, where the A(H3N2) were prevalent, particularly in the first half of the epidemic season. Later on, the situation in Europe has changed and, as in Russia, influenza B actively introduced in circulation. The proportion of isolation of influenza viruses A(H1N1) pdm09 in Russia was 69,2 %, of influenza A(H3N2) – 3,5 %, of influenza Вvic – 27,3 %. Activation of A(H1N1)pdm09 viruses was probably a result of emergence of drift-variants of this sub-type during the epidemics what was supported by the data of antigenic and genetic analyses. Thus in 2020 the first isolates of a genetic clade 6В.1А5а were discovered. They possessed the key substitution N156K in the antigenic site Sb of НА1. The results of genetic analysis have shown that among the A(H1N1)pdm09 viruses of the last season which belonged to the clade 6В.1А.5а.2а, a group of viruses carrying the substitutions P137S, K142R, D260E, T277A in HA1 could be found, which are also present in the new vaccine strain А/Victoria/4897/2022 (genetic sub-group 6В.1А.5а.2а.1). This virus was recommended for the next season 2023-2024 for the Northern Hemisphere. Concerning the antigenic properties, the viruses having such substitutions practically did not differ from the majority of strains A(H1N1)pdm09 in circulation during the last season. So influenza A(H1N1)pdm09 viruses, that circulated in Russia in 2022-2023 represented the antigenic cluster of A/Victoria/2570/2019-like strains. They were also similar to the strain A/Victoria/4897/2022, which was recommended by the WHO experts for the composition of vaccines for the season 2023–2024. The majority of viruses A(H3N2) have preserved the ability to agglutinate erythrocytes of mammals in the presence of 20 nM oseltamivir carboxylate, that is why we applied for their characterization the HI-test. The strains under study were very close to the strain A/Darwin/09/21, recommended by the WHO as the vaccine strain for the season 2022-2023. They belonged to the most wide-spread in the World genetic group 3С.2а1b.2a.2. All studied influenza B viruses belonged to the Victoria lineage and were B/Austria/1359417/2021-like. According to the phylogenetic analysis, all modern Victoria strains clustered into the sub-clade V1A.3a.2, coding the substitutions A127T, P144L и K203R in HA1. Inside this clade one can determine two genetic sub-groups: the 1st include viruses with the substitution in the HA1-protein D197E and the second – a group of viruses with the substitutions E128K, A154E, S208P in НА1. Strains of the Yamagata lineage were not registered on the territory of Russia since 2021, so the problem of their antigenic drift and possible return into circulation stays opened. The very low level of circulation of influenza viruses in 2020-2021 complicated the prognostics and selection of vaccine strains. According the results of HI- and MN-tests we could conclude that in 2021-2022 there was a partial consistency between the vaccine strain A/Cambodia/е0826360/20 (H3N2) and the strains in circulation which were more like to the reference strain A/ Darwin/9/21. We could also observe a mismatch of influenza viruses B in circulation and the vaccine variant B/Washington/02/19. As a result of the propagation of drift variants, the substitution of vaccine strains was made for the Northern Hemisphere for 2022/23. For the H3 component the strain A/Darwin/09/21 was introduced, and for Bvic component –B/Austria/1359417/21. Conclusion. In the period under consideration the relative homogeneity of population was observed inside each type and sub-type of influenza viruses and their fitness to the actual vaccine strains. However the selection of the strains – candidates for seasonal vaccines still remains a serious problem. Thus, in the season 2019-2020 one could observe a mismatch of the vaccine strain and the viruses in circulation in Russia for the component A(H3N2) and partial mismatch for the component B Victoria. In the season 2021-22 was evident a mismatch for Bvic and partial conformity for the component A(H3N2) and only in the last season 2022-23 we could confirm a complete fitness of the vaccine composition and the viruses in the circulation. The timely submission of data and samples to the WHO CCs promotes decision-making on the selection of strains and their introduction into influenza vaccines for the future epidemic season. The sustainability of the epidemiologic surveillance and the refinement of the methods of analysis of antigenic, genetic and other biological properties of circulating viruses would enhance the level of preparedness of healthcare system to the yearly influenza epidemics in the country.